PMO as a tool for the organizational knowledge management: case study in a project-based company of the sanitation service sector - de Lucca, Tácito Almeida; Hinnig, Marcus Phoebe Farias; Santos, Neri dos (International Journal of Project Management, 2020)
Purpose: In projected-based company, where all process dynamics and information flow are concentrated around projects, the role of the Project Management Office (PMO) becomes even more relevant. Precisely, the objective of the study was to highlight the importance of the PMO, as a tool in the management of organizational knowledge, in a research carried out, through a case study, in a project-based organization of the sanitation services sector. Methodology: The qualitative research method used the Project Management Maturity Model (MMGP) to assess the level of maturity in project management and to identify organizational and knowledge problems observed in the phases of the knowledge management process, with the application of an electronic questionnaire to verify the perception of the directors regarding the role of the PMO in knowledge management, coding and personalization as knowledge management strategies and the 5W2H quality tool for planning actions. Findings: The PMO's initiatives and practices in the organization under study resulted in an increase in the level of maturity in project management, in the total resolution of 70% of organizational problems and in the creation of a Knowledge Management System, confirming the relevant role of PMO in management organizational knowledge. Unique contribution to theory, practice and policy: The research has as a differential the use of the PMO as an instrument for the organizational knowledge management, a theme that lacks in the literature, as well as the exploration of knowledge management in the sanitation services sector. Another contribution is the application of the Project Management Maturity Model to assess the level of project management maturity and identify organizational and knowledge problems and observe the improvement after actions